Ginger (Zingiber Officinale) in Traditional Heritage: Exploring Local Knowledge and Usage Practices in the Community of Tarutung, Tapanuli Utara - Andreadi Simanjuntak , (Indonesian Journal of Medical Anthropology, 2024)
The use of ginger (Zingiber Officinale) as a traditional medicine and food ingredient has become an integral part of the lives of people in North Tapanuli, especially in the Tarutung area. This study highlights the local practices in the processing and use of ginger that have been passed down from generation to generation. Using literature review and observation methods, this research found that ginger has various health benefits, including treating coughs, colds, sore throats, diarrhea, and diabetes. Ginger is also popular in the form of beverages such as bandrek, which not only provides a delicious taste but also health benefits. Local knowledge about ginger processing and proper dosage is crucial to ensure the effectiveness of the treatment and avoid side effects. Therefore, the conservation and preservation of knowledge about ginger must continue to ensure its benefits can be enjoyed by future generations.